In dust and ashes - Holt, Anne, 1958- (Holt, Anne, 1958- Hanne Wilhelmsen novel., 2018)
"In 2001, three-year-old Dina is killed in a tragic car accident. Not long thereafter Dina's mother dies under mysterious circumstances, and Dina's father Jonas is convicted of her murder. Now its 2016, and the cold case ends up on the desk of Detective Henrik Holme, who tries to convince his mentor Hanne Wilhelmsen that Jonas might have been wrongly convicted. Holme and Wilhelmsen discover that the case could be connected to the suicide of an eccentric blogger, as well as the kidnapping of the grandson of a EuroJackpot millionaire"--Amazon.com.